Rapamycin reduces neuronal mutant huntingtin aggregation and ameliorates locomotor performance in Drosophila - Roth, Jonathan R.; Moraes, Ruan Carlos Macedo de; Xu, Brittney P.; Crawley, Savannah R.; Khan, Malghalara A.; Melkani, Girish C. (Frontiers in Aging Neuroscience, 2023)
Huntington’s disease (HD) is a neurodegenerative disease characterized by movement and cognitive dysfunction. HD is caused by a CAG expansion in exon 1 of the HTT gene that leads to a polyglutamine (PQ) repeat in the huntingtin protein, which aggregates in the brain and periphery. Previously, we used Drosophila models to determine that Htt-PQ aggregation in the heart causes shortened lifespan and cardiac dysfunction that is ameliorated by promoting chaperonin function or reducing oxidative stress. Here, we further study the role of neuronal mutant huntingtin and how it affects peripheral function. We overexpressed normal (Htt-PQ25) or expanded mutant (Htt-PQ72) exon 1 of huntingtin in Drosophila neurons and found that mutant huntingtin caused age-dependent Htt-PQ aggregation in the brain and could cause a loss of synapsin. To determine if this neuronal dysfunction led to peripheral dysfunction, we performed a negative geotaxis assay to measure locomotor performance and found that neuronal mutant huntingtin caused an age-dependent decrease in locomotor performance. Next, we found that rapamycin reduced Htt-PQ aggregation in the brain. These results demonstrate the role of neuronal Htt-PQ in dysfunction in models of HD, suggest that brain-periphery crosstalk could be important to the pathogenesis of HD, and show that rapamycin reduces mutant huntingtin aggregation in the brain.